Development of a spectrofluorimetric method for determination of thiabendazole in tablets - Semahat Kucukkolbasi and Esma Kilic (Journal of Applied Pharmaceutical Science, 2013)
In this study a spectrofluorimetric method has been developed for determination of thiabendazole drug active compound in tablets. For this purpose; thiabendazole drug active compound was measured fluorescence intensities at excitation (λex) and emission (λem) wavelength in various solvents. Suitable solvent was determined for each compound from calibration graphs and tablets' excipients. Spectrofluorimetric method for the determination of thiabendazole in tablet was described under the optimum conditions. The wavelengths of excitation and emission were 370,0 nm and 428.8 nm respectively. The fluorescence intensity was linearly related to the drug concentration and the method was found to be highly accurate and precise, having a relative standard deviation of less than 0.8 %. This proposed method was applied to the determination of thiabendazole in tablet. The validity of the method was tested by the recovery studies of standard addition to pharmaceuticals and the result was found to be satisfactory. The results compared with official USP 24 HPLC method were in good agreement and statistical comparison by means of Student’s t-test and the variance ratio F-test showed no significant difference between the two methods. The proposed method is simple and sufficiently precise for quality control purposes in routine analysis.
Keywords: Spectrofluorimetry, determination, thiabendazole, ph